Specific association of Piwi with rasiRNAs derived from retrotransposon and heterochromatic regions in the Drosophila genome. - Saito, K.; Nishida, K.M.; Mori, T.; Kawamura, Y.; Miyoshi, K.; Nagami, T.; Siomi, H.; Siomi, M.C. (Genes & Development, 2006)
In Drosophila, Piwi (P-element-induced wimpy testis), which encodes a protein of the Argonaute family, is essential for germ stem cell self-renewal. Piwi has recently been shown to be a nuclear protein involved in gene silencing of retrotransposons and controlling their mobilization in the male germline. However, little is known about the molecular mechanisms of Piwi-dependent gene silencing. Here we show that endogenous Piwi immunopurified from ovary specifically associates with small RNAs of 25-29 nucleotides in length. Piwi-associated small RNAs were identified by cloning and sequencing as repeat-associated small interfering RNAs (rasiRNAs) derived from repetitive regions, such as retrotransposon and heterochromatic regions, in the Drosophila genome. Northern blot analyses revealed that in vivo Piwi does not associate with microRNAs (miRNAs) and that guide siRNA was not loaded onto Piwi when siRNA duplex was added to ovary lysate. In vitro, recombinant Piwi exhibits target RNA cleavage activity. These data together imply that Piwi functions in nuclear RNA silencing as Slicer by associating specifically with rasiRNAs originating from repetitive targets.